"YouTube's predator problem": Platform moderation as governance-washing, and user resistance. (June 2022) - Tarvin, Emily; Stanfill, Mel
YouTube experienced large-scale criticism in early 2019 for predatory behavior toward children on the platform. To address concerns about children's safety, YouTube acted quickly by demonetizing and deactivating comments on videos featuring minors. In this paper, we analyze both the company's response to this scandal and how users received that response. We argue that YouTube's reaction was governance-washing, which presents the appearance of vigorous platform moderation and leverages popular perceptions of technology to create the look of authority while deflecting questions about substance. While YouTubers and users did not dispute that the pedophilic comments were heinous, they questioned the effectiveness of the company's solutions, arguing that YouTube's platform governance actions did not solve the problem. Ultimately, we show that users have cogent critiques of governance policies that pretend to be comprehensive but fail to solve what they purport to address, and offer up the term "governance-washing" as a useful framework to make sense of such cases.